Terahertz Reflectarray with Enhanced Bandwidth. Issue 20 (4th July 2019) - You, Xiaolong; Ako, Rajour T.; Lee, Wendy S. L.; Low, Mei Xian; Bhaskaran, Madhu; Sriram, Sharath; Fumeaux, Christophe; Withayachumnankul, Withawat
Abstract: Reflectarrays offer unique potential for beamforming at terahertz frequencies as they combine the advantages of low‐profile of phased arrays and high‐efficiency of parabolic antennas. However, one challenge associated with reflectarrays is their bandwidth limitation resulting from the nonlinear phase response. To enhance bandwidth, a single‐layer stub‐loaded resonator is proposed for constructing reflectarrays. This resonator design shows a smooth and near‐linear phase response with a complete 360° phase coverage at and around the design frequency. To demonstrate its capability in realizing beamforming, a focusing reflectarray is then constructed using the proposed resonator as a building block. The measured results reveal that the 3 dB relative bandwidths of the reflectarray for the transverse electric (TE)‐ and transverse magnetic (TM)‐polarized excitations are 23.3% and 23.9%, respectively, while retaining an efficiency of 71.9% for the TE polarization and 71.0% for the TM polarization at the center frequency of 1.00 THz. The simulation bandwidth of this proposed focusing reflectarray is over twice that of an existing dielectric resonator reflectarray. The proposed resonator has a potential to enhance the bandwidth of terahertz reflectarrays for various beamforming functions. Abstract : Fabricated focusing reflectarray consisting of metallic stub‐loaded resonators . This single‐layer terahertz reflectarray is made of sub‐wavelength resonators with enhanced bandwidth. A focusing reflectarray is constructed as a platform using the proposed resonators to focus an incident collimated beam into a point, exhibiting an improved bandwidth performance. Potential applications of the proposed resonator include terahertz communications, sensing, and imaging.